AB0337 Improving the Quality and Efficiency of Clinic Visits for IA Patients by Preparing for their Visit. (9th June 2015) - Orr, C.; Young, F.; MacMullan, P.; O'Dwyer, E.; Veale, D.J.
Abstract : Background: Treatment decisions in clinic, in line with the EULAR Treat-to Target recommendations, 1 require access in the clinic to CRP/ESR, the patient global assessment (visual analogue scale), in addition to joint counts. In practice, the CRP/ESR are often not readily available, thus preventing the calculation of disease activity scores (DAS) at that time. In addition, radiographic progression of erosive disease is also helpful to inform decisions. The potential benefits of using an empirical method to treat patients and compare DAS between visits and after commencing new therapies are readily apparent. 2 Changing practice to calculating DAS28-CRP scores for all return IA patients will therefore result in a demonstrable increase in quality of care. Objectives: To increase consult quality and efficiency by: Ensuring the availability at the time of consultation of recent inflammatory markers, full serology where relevant, and radiographs of hands and feet taken within the last 36 months. Routinely calculating DAS for all IA patients in clinic. Methods: Returning IA patients where identified 2 weeks before their scheduled visit. The patient's blood results were accessed through the hospital's laboratory database. If the patient had an ESR and CRP within the last two weeks (and so within 4 weeks of their clinic visit), it was accepted that this likely represents an accurate result for the purposes of their clinic visit. If the results were more than 2 weeks old, or abnormal, new blood ordering forms for these tests were prepared and sent to the patient by post. RF and anti-CCP, were also requested if appropriate and not yet done. The last set of hands and feet plain film radiographs were identified for each patient by searching the hospital's radiology database. If they were performed anytime within the last 36 months, they were recorded as such, but if not, the patients were posted a request form. An explanatory letter accompanied these forms was also sent. Results: 131 patients (85 female) were included. 77 had RA, 43 PsA, 2 undifferentiated arthritis, 1 connective tissue disease, 1 gout, 1 juvenile idiopathic arthritis, 4 OA (erosive), and 2 had no diagnosis recorded. 120 (91.6%), patients had with DAS28-CRP scores calculated, 7 (5.34%) did not have scores calculated because of a piece of essential missing data, and it was thought not appropriate to calculate a score for those 4 (3.05%) who had osteoarthritis. No radiographs were available for 68/131 (51.9%) in the three 3 years before the clinic visit. Of these, 49 (72.1%) had radiographs directly as a result of this change project. The overall compliance with the policy of obtaining staging radiographs every two years is now 92.4%, which represents an improvement of 40.5%. Conclusions: This new system for reviewing patients has ensured that clinicians have access to full DAS and radiographic profiling of the pathology. This has improved the quality and efficiency of clinic decisions. References: Smolen, J. S. et al. Treating rheumatoid arthritis to target: recommendations of an international task force. Annals of the Rheumatic Diseases (2010)., 69(4), 631-637 Mierau M, et al. Assessing remission in clinical practice. Rheumatology (Oxford) 2007;46:975–9. Disclosure of Interest: None declared